Method for constructing ultra-low-loss through hole in thick electrode through time / frequency shaping laser
The method of building ultra-low loss through holes on thick electrodes through time/frequency shaping laser technology solves the problem of excessive pore loss in traditional methods, and improves the energy density and cycle life of thick electrodes.
Patent Information
- Application Number
- CN202411869349.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-18
AI Technical Summary
In the prior art, when preparing pore structures on thick electrodes, the pore loss is too high (20%-40%) and cannot be calendered, resulting in a decrease in the energy density and cycle life of the battery.
The method of using time/frequency shaping laser technology to build ultra-low loss through-holes on thick electrodes is used to shape the lasers with a loss control of less than 1% through birefringent crystals, BBO, high-power objective lenses and other components.
The power density, energy density and cycle life of thick electrodes are improved, the loss of active substances is reduced, and the rate performance and cycle stability of the battery are improved.
Smart Images

Figure CN119794622A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for constructing an ultra-low loss through hole on a thick electrode by using a time / frequency shaping laser, and belongs to the technical field of laser processing of electrode materials. Background Art
[0002] Portable electronic products, electric vehicles and large-scale energy storage systems have put forward higher requirements for the energy density and power density of batteries while ensuring safety. Thick electrodes can improve the energy density of batteries, but their high tortuosity is seriously unfavorable to the penetration of electrolytes and the migration of lithium ions, reducing their rate performance and capacity. In addition, the gaps between the powders of traditional electrodes are easily blocked during long cycles due to the negative reaction between materials and electrolytes, which ultimately leads to poor cycle life. The introduction of pore structures with low tortuosity can solve this problem. Specific methods include template method, 3D printing method and other methods. These methods have the problems of complex preparation steps, incompatibility with calendering process, and excessively high pore loss rate.
[0003] By utilizing the interaction between high-energy laser beams and materials, geometric structures such as grooves, holes, lines, and grids at the micron level can be constructed to achieve high-precision, pollution-free processing of thick electrode structures on the electrode surface. However, this manufacturing process will cause the loss of active materials and reduce energy density. Take the battery with LFP as the positive electrode and lithium metal as the negative electrode as an example: when the thickness of the LFP electrode layer increases from 60μm to 260μm, the weight energy density can increase by 45.6%. When the introduced pore loss increases to 20%, the energy density will be reduced by 16.9%, which seriously weakens the improvement in energy density brought by the thick electrode. A pore loss of 1% hardly reduces the improvement in energy density brought by the thick electrode. Therefore, optimizing laser parameters and process flow and preparing low-loss pore structures on thick electrodes to reduce the loss of active materials are the key to the commercial application of this technology, which can achieve improvements in power density, energy density, and cycle life of thick electrodes.
[0004] Traditional punching methods include single-pulse punching, multi-pulse punching, circular cutting punching and spiral punching. Single-pulse punching is suitable for relatively thin materials, and the thickness of the plate can be penetrated by one pulse. Circular cutting punching and spiral punching are suitable for the construction of large-sized apertures. Although multi-pulse punching is suitable for the construction of small holes, the depth of laser drilling is limited due to the shielding effect of plasma on subsequent lasers during the processing process. In addition, the electrode material is a powder material that is relatively easy to process. It is very difficult to use conventional laser drilling methods to process ultra-low loss apertures on thick electrodes. Summary of the invention
[0005] In order to solve the problem that the pore loss introduced by traditional methods such as template method and 3D printing method in thick electrodes is too high (20%-40%) and cannot be rolled, the conventional laser drilling method processes ultra-low loss apertures on thick electrodes. The present invention uses a method of constructing ultra-low loss through holes on thick electrodes by time / frequency shaping laser, and prepares ultra-low loss and low tortuosity pore structures on thick electrodes, with the loss controlled within 1%, reducing the problem of excessive loss of active materials caused by traditional pore manufacturing methods on thick electrodes, and achieving the improvement of power density, energy density and cycle life of thick electrodes.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] The present invention discloses a method for constructing ultra-low loss through-holes on thick electrodes by using time / frequency shaping lasers. The method uses birefringent crystals, BBO, and high-power objective lenses to time-frequency shape traditional Gaussian lasers into short-wavelength lasers with certain delay and focal depth. Harmonic beam splitting is used to improve the optical path of the commonly used BBO combined with a filter to perform energy protection to curb the safety problems caused by reflected light under high energy. The aperture limiter is used to ensure that the laser with high single pulse energy is used while reducing the spot diameter, so as to realize the preparation of ultra-low loss and low tortuosity pore structures on thick electrodes, and the loss is controlled within 1%. The present invention solves the safety problems caused by the energy of short-wavelength lasers, reduces the problem of excessive pore loss (20%-40%) and inability to roll introduced by traditional methods such as template method and 3D printing method in thick electrodes, solves the decrease in capacity and rate performance of thick electrodes due to electrolyte penetration difficulties and increased lithium ion transmission distance, and improves the power density, energy density, and cycle life of thick electrodes.
[0008] Furthermore, the ultra-low loss and low tortuosity pore structure with loss controlled within 1% on the thick electrode is specifically constructed to consist of through holes with a diameter of 5-6 μm and a pore spacing of 60 μm, and all the pores are through holes.
[0009] Furthermore, in the method, the thickness of the thick electrode is adjusted according to the requirements of the energy density and power density of the actual battery, and the range is 60 μm-260 μm.
[0010] A method for constructing an ultra-low loss through hole on a thick electrode using a time / frequency shaping laser, comprising the following steps:
[0011] Step 1: Use birefringent crystals to change the time delay between pulsed lasers and BBO to double the laser wavelength, and combine high-power objective lenses, harmonic beam splitting, and limited apertures to build a time / frequency shaping laser femtosecond laser system;
[0012] Step 2: Focus the time / frequency shaped femtosecond laser on the surface of the thick electrode to perform multi-pulse impact drilling. After optimization, ultra-low loss and low tortuosity through-hole pore structures are obtained on thick electrodes of different thicknesses;
[0013] Step 3: Assemble in the order of positive electrode shell-LFP positive electrode sheet-diaphragm-negative electrode sheet-gasket-spring sheet-negative electrode shell, add appropriate amount of electrolyte during the process, and assemble into a button battery;
[0014] Step 4: Assemble the untreated electrode and the electrode with processed pore array into a battery, and perform rate test and cycle stability test using a blue battery tester.
[0015] Furthermore, the time / frequency shaping laser femtosecond laser system includes a femtosecond laser, an attenuation plate, a BBO, a harmonic beam splitter, a birefringent crystal, a mechanical switch, an ultrafast reflector group, an aperture, a dichroic mirror, a high-power objective lens, an electrode material, a three-dimensional precision displacement stage, a beam splitter, white light, and a CCD dynamic imaging unit; the BBO converts an 800nm femtosecond laser into a mixed laser of 800nm and 400nm, the harmonic beam splitter reflects the 400nm femtosecond laser onto the birefringent crystal and converts it into a time-domain shaped femtosecond laser with a certain delay, and after passing through an aperture of a limited size and entering the dichroic mirror, it is focused on the electrode sample located on the precision displacement stage on the high-power objective lens; the white light source passes through the beam splitter, the dichroic mirror, and the CCD dynamic imaging unit to jointly realize real-time imaging and monitoring of laser drilling on the electrode surface.
[0016] Furthermore, the birefringent crystal shapes the conventional pulsed laser into a laser pulse with a delay within 10ps; the harmonic beam splitting simultaneously realizes the reflection of 400nm laser and the transmission of 800nm laser; the aperture size is controlled at 2mm-3mm.
[0017] Beneficial effects:
[0018] 1. The present invention discloses a method for constructing ultra-low loss through-holes on thick electrodes by using time / frequency shaping lasers. The time / frequency shaping laser femtosecond laser system used includes a femtosecond laser, an attenuator, a BBO, a harmonic beam splitter, a birefringent crystal, a mechanical switch, an ultrafast reflector group, an aperture, a dichroic mirror, a high-power objective lens, an electrode material, a three-dimensional precision translation stage, a beam splitter, white light, and a CCD dynamic imaging unit. The time / frequency shaping laser generated by the system has the advantages of a sub-pulse sequence with a ps delay and a small spot diameter. The time-domain shaped femtosecond laser has a sub-pulse sequence with a ps delay that minimizes the reflection of the laser by the plasma, thereby promoting more efficient energy transfer to the bottom of the hole, which is beneficial for processing high aspect ratio through-holes; the frequency-domain shaped femtosecond laser has a small spot diameter and can prepare ultra-low loss and low tortuosity through-holes on different thick electrodes, reducing the loss of active substances; harmonic beam splitting is used to improve the optical path of the commonly used BBO combined with filters for energy protection to curb the safety problems caused by reflected light under high energy; the aperture limiting approach ensures the use of high single pulse energy lasers while reducing the spot diameter.
[0019] 2. The present invention discloses a method for constructing ultra-low loss through holes on thick electrodes using a time / frequency shaping laser. In this method, it is difficult to manufacture low-loss high aspect ratio through holes on thick electrodes. Using this method, ultra-low loss, low tortuosity pore structures with a loss control within 1% are prepared on electrodes of different thicknesses. The specific structure consists of through holes with a diameter of 5-6μm and a pore spacing of 60μm, and all pores are through holes. The thickest electrode thickness is 260μm, and the current collector thickness is 20μm. The low-loss pore structure prepared under this condition has an aspect ratio of up to 47, which is the highest aspect ratio among through hole structures prepared in current opaque materials.
[0020] 3. The present invention discloses a method for constructing ultra-low loss through holes on thick electrodes using a time / frequency shaping laser. The electrode with a pore array prepared by the method and the untreated electrode are assembled into batteries, respectively, to achieve the improvement of the power density, energy density and cycle life of the thick electrode. The through hole provides a shorter diffusion path for lithium ions, significantly reducing the internal resistance, thereby achieving a faster charge and discharge rate; in terms of energy density, reducing the internal resistance of the electrode and enhancing ion diffusion make it possible to use thicker electrodes, and thick electrodes can increase the proportion of active materials in the entire battery, thereby improving the overall energy density; the gaps between the powders of traditional electrodes are easily blocked during long-term cycles due to the negative reaction between the material and the electrolyte, and the through-hole structure is not easily blocked, thereby ensuring smooth diffusion of ions and more stable cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of a method for constructing ultra-low loss through holes on thick electrodes using time / frequency shaping lasers.
[0022] Figure 2 Relationship between thick electrode thickness, porosity loss rate and battery energy density.
[0023] Figure 3 Schematic diagram of the optical path of the time / frequency shaping femtosecond laser in the present invention.
[0024] Figure 4 The pore array morphology of a low-loss thick electrode with a thickness of 280 μm.
[0025] Figure 5 Comparison of battery rate performance of low-loss thick electrodes of different thicknesses and untreated electrodes.
[0026] Figure 6 Comparison of the cycle life of low-loss thick electrodes of different thicknesses and untreated electrodes.
[0027] Among them: 1—femtosecond laser, 2—attenuation plate, 3—BBO, 4—harmonic beam splitter, 5—birefringent crystal, 6—mechanical switch, 7—ultrafast reflection mirror group, 8—aperture, 9—dichroic mirror, 10—high-power objective lens, 11—electrode material, 12—three-dimensional precision translation stage, 13—beam splitter, 14—white light, 15—CCD dynamic imaging unit, 16—baffle. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to the accompanying drawings and embodiments, but the embodiments of the present invention are not therefore limited to the following embodiments.
[0029] like Figure 1 As shown, the present embodiment discloses a method for constructing an ultra-low loss through hole on a thick electrode by using a time / frequency shaping laser. A birefringent crystal, BBO, and a high-power objective lens are used to time-frequency shape a traditional Gaussian laser into a short-wavelength laser with a certain delay and focal depth. Harmonic beam splitting is used to improve the optical path of the commonly used BBO combined with a filter to perform energy protection to curb the safety problems caused by reflected light under high energy. A limited aperture is used to ensure that a laser with high single pulse energy is used while reducing the spot diameter. This realizes the preparation of an ultra-low loss and low tortuosity pore structure on a thick electrode, and the loss is controlled within 1%, thereby improving the power density, energy density, and cycle life of the thick electrode.
[0030] The introduction of pore structures on thick electrodes will help solve the problem of decreased capacity and rate performance due to difficulty in electrolyte penetration and increased lithium ion transmission distance, but the introduction of pores will also lead to loss of active materials and reduce energy density. Figure 2As shown in the figure, taking a battery with LFP (LiFePO4, lithium iron phosphate) as the positive electrode and lithium metal as the negative electrode as an example: when the thickness of the LFP electrode layer increases from 60μm to 260μm, the weight energy density can increase by 45.6%. When the introduced pore loss increases to 20%, the energy density will decrease by 16.9%, which seriously weakens the energy density improvement brought by the thick electrode. The pore loss of 1% hardly reduces the energy density improvement brought by the thick electrode.
[0031] This embodiment discloses a method for constructing an ultra-low loss through hole on a thick electrode using a time / frequency shaping laser, and the specific implementation steps are as follows:
[0032] Step 1: The time / frequency domain shaping femtosecond laser system (such as Figure 3 The device (as shown) includes a femtosecond laser 1, an attenuation plate 2, BBO (BaB2O4) 3, a harmonic beam splitter 4, a birefringent crystal 5, a mechanical switch 6, an ultrafast reflection mirror group 7, an aperture 8, a dichroic mirror 9, a high-power objective lens 10, an electrode material 11, a three-dimensional precision translation stage 12, a beam splitter 13, white light 14, and a CCD dynamic imaging unit 15. The 800nm femtosecond laser emitted by the femtosecond laser 1 passes through the attenuation plate 2 and is converted into a mixed laser of 800nm and 400nm through the BBO 3; the mixed laser is separated into a transmitted laser of 800nm and a reflected laser of 400nm through the harmonic beam splitter 4, and the 400nm laser is converted into a time-domain shaped femtosecond laser with a delay of 0.45ps through the birefringent crystal 5 with a thickness of 0.8mm; the time / frequency shaped femtosecond laser passes through the mechanical switch 6 and enters the reflector group 7 and then enters the aperture 8 limited to 2-3mm in size; the laser passes through the dichroic mirror 9 and enters the high-power objective lens 10 and is focused on the electrode sample 11 located on the precision displacement stage 12. The white light source 14 passes through the beam splitter 13, the dichroic mirror 9, and the CCD dynamic imaging unit 15 to jointly realize the real-time imaging and monitoring of the time / frequency shaped femtosecond laser drilling on the electrode surface. The 800nm transmitted laser is shielded by a baffle 16, thereby achieving energy protection to curb the safety problems caused by reflected light at high energy.
[0033] The time domain shaping method is not limited to birefringent crystals. Other methods such as Michelson interferometer, spatial light modulator, and film-based design can also shape traditional lasers into a sequence of sub-pulses with a certain delay. Frequency domain shaping is not limited to BBO doubling. Tripling or quadrupling the long wavelength laser to a short wavelength laser all belong to frequency domain shaping.
[0034] Step 2: Prepare in advance different thicknesses (130 μm, 170 μm, 260 μm; Al foil 20 μm; corresponding surface density 30 mg cm -2 , 40mg cm -2 、60mg cm -2) LFP electrode. The femtosecond laser after time / frequency shaping is focused on the surface of the thick electrode to perform multi-pulse impact drilling. After optimization, ultra-low loss and low tortuosity pore structure arrays are obtained on thick electrodes of different thicknesses, and the loss is controlled within 1%. The structure of the pore array under this loss is composed of through holes with a diameter of 5-6μm and a pore spacing of 60μm. At 60mg cm -2 For example, Figure 4 The scanning electron microscope results shown in the figure show that the surface morphology of the through-hole array prepared by femtosecond laser after time / frequency shaping is uniform and there are no microcracks, material peeling and other problems. The results of tomography show that the introduction of through-holes greatly reduces the tortuosity of the electrode, and can achieve a through-hole with a depth-to-diameter ratio of up to 47 on LFP. This depth-to-diameter ratio is the highest among the through-hole structures prepared in the current opaque materials and is conducive to the penetration of electrolyte and the migration of lithium ions.
[0035] In this embodiment, four thicknesses are selected for manufacturing ultra-low loss and low tortuosity pores on the LFP electrode. The method is not limited to these four electrode thicknesses, and is applicable to electrodes in the range of 60 μm-260 μm and other thicknesses.
[0036] Step 3: Assemble in the order of positive electrode shell-LFP positive electrode sheet (5×5mm)-diaphragm-negative electrode sheet (lithium sheet)-gasket-spring sheet-negative electrode shell, add 30μL of lithium hexafluorophosphate LiPF6 (ethylene carbonate EC: diethyl carbonate DEC=1:1) electrolyte during the process, and assemble into a button battery. The LFP electrode without laser treatment and the ultra-low loss and low tortuosity LFP electrode prepared by time / frequency shaping femtosecond laser are assembled into button batteries respectively.
[0037] Step 4: Test the performance of the assembled battery using a blue battery tester. The low-loss, low-tortuosity thick electrode has higher power density, energy density, and cycle life than the untreated electrode. This is because the introduction of the pore structure on the thick electrode is conducive to the penetration of the electrolyte, shortens the migration distance of lithium ions, reduces the loss of active substances, and evens out the lithium ion flux. Specifically, Figure 5 As shown in Figure 2, electrodes of different thicknesses exhibit significant differences in rate performance. The 130 μm laser-processed LFP electrode achieved 128, 97, and 41 mAh g at 1C, 2C, and 3C, respectively. -1 The specific capacities of the untreated electrodes were only 113, 50 and 15 mAh g -1 The LFP electrode processed by 170 μm laser achieved 130, 113 and 78 mAh g at 1C, 1.5C and 2C, respectively. -1 The specific capacities of the untreated electrodes were only 51, 20, and 9 mAh g -1 The capacity of the LFP electrode processed by 260 μm laser is 85 mAh g at 1.5C.-1 The capacity of the untreated electrode is 8 mAh g -1 The through-holes provide a shorter diffusion path for ions, significantly reducing the internal resistance, thus achieving a faster charge and discharge rate. The ultra-low-loss, low-tortuosity pore structure prepared by time / frequency shaping femtosecond laser can increase the power density of thick electrodes by 100-200% without affecting the specific capacity. -1 Under the condition of acceptable battery capacity, thicker electrodes are allowed to be put into use. For example, under 2C conditions, the thickness can be increased from 95μm to 185μm, that is, the energy density is increased by 17.26%. Reducing the internal resistance of the electrode and enhancing ion diffusion make it possible to use thicker electrodes, increase the proportion of active materials in the battery, and thus improve the energy density of the battery.
[0038] The results of the cyclic stability test of LFP electrodes with different thicknesses (130 μm, 170 μm, 260 μm) are shown in Figure 6 As shown. Compared with the unstructured electrode, the laser-structured LFP electrode also shows superior cycling performance. At a rate of 0.2C, all thick electrodes with unstructured structures can only maintain 40-60 cycles, while the laser-structured electrodes can cycle up to 150 times. The gaps between the powders of traditional electrodes are easily blocked during long-term cycles due to the negative reaction between the material and the electrolyte. The low-loss and low-tortuosity pore structure processed by laser is conducive to homogenizing the lithium ion flow and inhibiting the growth of lithium dendrites, thereby significantly improving the cycle life.
[0039] In this embodiment, the electrode material selected is LFP electrode material. A method of constructing ultra-low loss through holes on thick electrodes using a time / frequency shaping laser can also be applied to pore manufacturing of other electrode materials, such as ternary electrodes (NMC811).
[0040] The specific description above further illustrates the purpose, technical solutions and beneficial effects of the invention in detail. It should be understood that the above is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for constructing ultra-low loss through holes on thick electrodes using time / frequency shaping lasers, characterized in that: Birefringent crystals, BBO and high-power objective lenses are used to time-frequency reshape the traditional Gaussian laser into a short-wavelength laser with a certain delay and focal depth. Harmonic beam splitting is used to improve the optical path of BBO combined with filters for energy protection. The aperture limiting approach is used to ensure the use of high single-pulse energy laser while reducing the spot diameter, so as to achieve the preparation of ultra-low loss and low tortuosity pore structures on thick electrodes, and the loss is controlled within 1%.
2. A method for constructing ultra-low loss through holes on thick electrodes using time / frequency shaping lasers as claimed in claim 1, characterized in that: The ultra-low loss and low tortuosity pore structure with loss controlled within 1% on the thick electrode is specifically constructed of through holes with a diameter of 5-6μm and a pore spacing of 60μm, and all the pores are through holes.
3. A method for constructing ultra-low loss through holes on thick electrodes using time / frequency shaping lasers as claimed in claim 2, characterized in that: The thickness of the thick electrode is adjusted according to the energy density and power density requirements of the actual battery, ranging from 60μm to 260μm.
4. The method according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1: Use birefringent crystals to change the time delay between pulsed lasers and BBO to double the laser wavelength, and combine high-power objective lenses, harmonic beam splitting, and limited apertures to build a time / frequency shaping laser femtosecond laser system; Step 2: Focus the time / frequency shaped femtosecond laser on the surface of the thick electrode to perform multi-pulse impact drilling. After optimization, ultra-low loss and low tortuosity through-hole pore structures are obtained on thick electrodes of different thicknesses; Step 3: Assemble in the order of positive electrode shell-LFP positive electrode sheet-diaphragm-negative electrode sheet-gasket-spring sheet-negative electrode shell, add appropriate amount of electrolyte during the process, and assemble into a button battery; Step 4: Assemble the untreated electrode and the electrode with processed pore array into a battery, and perform rate test and cycle stability test using a blue battery tester.
5. The method according to claim 4, characterized in that In the time / frequency shaping laser femtosecond laser system, BBO converts 800nm femtosecond laser into mixed laser of 800nm and 400nm, and harmonic beam splitting reflects 400nm femtosecond laser onto a birefringent crystal to convert it into a time-domain shaped femtosecond laser with a certain delay, which enters a dichroic mirror through an aperture of a limited size and is focused on an electrode sample on a high-power objective lens on a precision displacement stage; a white light source is passed through a beam splitter, a dichroic mirror, and a CCD dynamic imaging unit to realize real-time imaging and monitoring of laser drilling on the electrode surface.
6. The method according to claim 5, characterized in that The birefringent crystal shapes the pulsed laser into a laser pulse with a delay within 10ps; the harmonic beam splitting simultaneously reflects the 400nm laser and transmits the 800nm laser; the aperture size is controlled at 2mm-3mm.
Citation Information
Patent Citations
System and method for peeling LED substrates by using laser
CN102699537A
Method for efficiently processing high-quality micro hole with large ratio of pit-depth to pit-diameter through femtosecond laser
CN103878496A
Method for efficiently making large-depth-diameter-ratio micropore arrays
CN105458529A
Wavelength coded probe light generation device
CN115128001A
Method for high-quality processing of CFRP based on time-domain shaping femtosecond laser
CN116060758A